NEW FLORISTIC RECORDS TO DAGESTAN - A. A. Teimurov; L. L. Satueva; D. M. Mirzaev; Z. I. Soltanmuradova (Юг России: экология, развитие)
Abstract. Information on some new species to Dagestan flora, recently revealed during field investigations is presented.